A Severe Case of Arthrographis kalrae Keratomycosis - Ramli, Siti Roszilawati (Hindawi Publishing Corporation, 2013)
A 52-year-old man with diabetes developed a unilateral central corneal ulcer after accidental foreign body inoculation. He complained of pain and loss of visual acuity in the injured eye, which displayed redness and edema and eventually discharged pus. A corneal scraping from the left eye orbit revealed fungal elements, and cultures of the material grew a fungus. The isolate was identified as Arthrographis kalrae based on gross and microscopic morphologies. The patient received amphotericin B intravenously and itraconazole orally. The wound healed following surgical intervention, but the patient lost the use of his left eye.